2018
DOI: 10.1002/smll.201800697
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma‐Like MoS2/NiS2 with Single Platinum Atoms Doping as an Efficient and Stable Hydrogen Evolution Reaction Catalyst

Abstract: Herein, a unique ganoderma-like MoS /NiS hetero-nanostructure with isolated Pt atoms anchored is reported. This novel ganoderma-like heterostructure can not only efficiently disperse and confine the few-layer MoS nanosheets to fully expose the edge sites of MoS , and provide more opportunity to capture the Pt atoms, but also tune the electronic structure to modify the catalytic activity. Because of the favorable dispersibility and exposed large specific surface area, single Pt atoms can be easily anchored on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 29 publications
3
43
0
1
Order By: Relevance
“…The result of elemental analysis (EA) revealed 5.17 wt% nitrogen content of in Pt 1 /N–C (Supplementary Table 2). High BET area (595 m 2 g –1 ) was found for Pt 1 /N–C (Supplementary Table 2), and it was reported that high-surface-area structures could facilitate the atomic dispersion of metal species 37 .…”
Section: Resultsmentioning
confidence: 95%
“…The result of elemental analysis (EA) revealed 5.17 wt% nitrogen content of in Pt 1 /N–C (Supplementary Table 2). High BET area (595 m 2 g –1 ) was found for Pt 1 /N–C (Supplementary Table 2), and it was reported that high-surface-area structures could facilitate the atomic dispersion of metal species 37 .…”
Section: Resultsmentioning
confidence: 95%
“…Single metal atom doped MoS 2 have been also demonstrated to be highly efficient electrocatalysts toward HER. The metal atoms mainly acted as modifiers to modulate the electronic structure and trigger the activity enhancement of the MoS 2 support, which was first reported by Deng et al Since then, several kinds of Pt, Pd, Ni, Fe, and Mn atoms modified MoS 2 have been synthesized and evacuated their HER activity 64,65b,66–68. Experimental and theoretical results suggested that 1) metal substitution occurs at the molybdenum site, simultaneously optimizing the adsorption behavior of H* on the neighboring S active sites, and 2) the metal atom doping may induce the phase transformation from 2H to 1T, thus improving the conductivity.…”
Section: Electrocatalytic Performancementioning
confidence: 94%
“…In other works, Mn atom doped MoS 2 and Ni atom doped SnS 2 have been obtained by hydrothermal method . For another method, atom doped TMDs were obtained through doping metal atom into the as‐prepared TMDs by calcination, such as the Co, Pt, and Ni atom doped MoS 2 and WS 2 . For example, Luo et al synthesized Pd atom doped MoS 2 through ultrasonic mixing of as‐prepared MoS 2 and Pd(OAc) 2 , followed by thermal treatment at 60 °C .…”
Section: Synthesis Of Sacs In 2d Materialsmentioning
confidence: 99%
“…On the basis of theoretical studies, the Gibbs free energy change of H‐adsorption (Δ G H ) on surface sites is related to the HER activity of a catalyst . The MH bond should be neither too strong nor too weak to achieve the optimal performance, which obeys the Sabatier principle in catalysis .…”
Section: Introductionmentioning
confidence: 99%